Hierarchy Website Fingerprint Using N-gram Byte Distribution - Aldarwbi, Mohammed; Shahra, Essa (Discoveries in Agriculture and Food Sciences, 2017)
According to www.internetlivestats.com, there are over 1 billion websites on the world wide web (WWW) today while in 1991, there were only one single website. Websites classification based on traffic analysis has become a difficult problem due to the large number of websites within the internet. All the proposed approaches in the literature could not classify more than 100 websites which is a very trivial number compared to the total number of websites over the internet. In this paper, a two-level websites’ classification technique is proposed. At the first level, the traffic is classified to a general category such as sports, news, social, healthy, education, etc. Then, for further information the packet could be classified within the same category to identify from which websites the packet came.